Multi-objective optimisation of process parameters in turning of Al6061 alloys using DEFORM-3D. (10th December 2020) - Sahu, Manoj; Bhanot, Neeraj; Mahanta, Bashista Kumar
Turning operation is one of the most widely used machining processes in manufacturing industries wherein optimisation of process parameters is the most critical aspect within the operational constraints. In this paper, finite element simulations have been carried out for dry turning of Al6061 alloy with uncoated tungsten carbide inserts to predict the performance of machining. Thus, the effect of process parameters such as cutting speed, feed rate and depth of cut on response variables such as cutting temperature, cutting energy, effective stress, material removal rate and tool life have been studied by employing Taguchi L25 orthogonal array. Grey relational analysis has been further used to convert multi responses parameters to a single response for optimising the process parameters using particle swarm optimisation. The results of the study indicated that the cutting speed of 40 m/min, feed rate of 0.04 mm/rev and 0.5 mm depth of cut provides better machining performance based on the application of simulation approach leading to time saving and efficient utilisation of resources.